Electric current measurement using fiber-optic curvature sensor. (February 2016) - Di, Haiting; Xin, Ying; Sun, Suping
Abstract: A novel fiber-optic curvature sensor, which can measure curvature directly, has been developed in recent years. The electric current measurements system based on fiber-optic curvature sensor and electromagnetic principle is developed. A fiber-optic curvature sensor is bonded to a thin-walled cantilever and two circular magnet targets with the same parameters are configured at the tip of the cantilever symmetrically. In this case, the throughput of the sensor will be changed due to the bending deformation of cantilever, which is proportional to the electromagnetic force caused by measured electric current. Direct and alternate characteristics of the proposed measurement system are studied experimentally. The results show that the measurement errors are within the range of ±5.5 mA and the corresponding accuracy is within 1% at the current measurement range from −300 mA to 300 mA, which indicate the feasibility of the proposed measurement system. Highlights: A current measurement system based on fiber-optic curvature sensor is developed. There is a linear relationship between the output of sensor and measured current. The proposed system can measure intensity and direction of current simultaneously. Measurement accuracy is within 1% at the current range from −300 mA to 300 mA. The response of the measurement system to sine signal is satisfying.